Efeitos das variações sazonais do clima tropical úmido sobre as águas e sedimentos de manguezais do estuário do rio Marapanim, costa nordeste do Estado do Pará - SILVA, José Francisco Berrêdo Reis da (Instituto Nacional de Pesquisas da Amazônia, 2014)
To evaluate the short period climatic variations impact over Amazonic mangrove ecosystem, studies were carried out on the northeast coast of Para State. Sediments, surficial and interstitial waters were collected and examinated throughout salinity, pH and Eh (mV) measurements; mineralogical determination using X-ray diffraction and electronic microscopy. Chemical analysis of dissolved sulfides, sulfate and chloride, among others were made in samples collected seasonally, under spring and neap tides conditions. The seasonal chloride variations in the interstitial waters shows 20 g/l during the dry season and less of 10 g/l in the season; the concentration in surficial are higher at neap tides (rainy season) and spring tide (dry season). The dissolved sulfides were found only at 10 cm, indicating sediment exposure to the atmospheric oxygen advectives fluxes. The dissolved iron rates increases between 0-10 cm and the pH tends to neutrality. The saturation of interstitial waters at dry season is indicated by evaporitic minerals: gypsum and halite. The pluviometric variations are responsible by gradual changes in the nutrient and physical chemical properties of surficial and interstitial waters, into the saline equilibrium control at coastal waters, in the salinization and desalinization of sediments and the distribution of mangrove vegetation at the estuary. The prolonged exposure of sediments during the dry season and the morphological characteristics contribute to the total or partial oxidation of surficial sediments, modifying the mineralogy of sediments and the physical chemical characteristics of interstitial waters.